A fluorescent molecular rotor showing vapochromism, aggregation-induced emission, and environmental sensing in living cells - König, Matthias; Storti, Barbara; Bizzarri, Ranieri; Guldi, Dirk Michael; Brancato, Giuseppe; Bottari, Giovanni (Journal of Materials Chemistry C, 2016)
Among the plethora of recently proposed molecular sensors, those belonging to the class of fluorescent molecular rotors (FMRs) have attracted much attention owing to their peculiar photophysical properties that enable an unprecedented sensitivity towards environmental microviscosity. The usual FMR synthetic design prescribes chromophores characterized by an intramolecular rotation between two well-defined excited states, a locally excited state and a twisted internal charge transfer (TICT) state, where the sensing capabilities arise from a dual competition of the corresponding radiative/non-radiative decay processes. However, we have recently demonstrated a different modus operandi of a new subclass of solvatochromic FMRs, which exploit a solvent-independent, barrier-free intramolecular rotation of the excited dye. The rotational dynamics is modulated by local viscosity and, in turn, manifested through a variable spectral signal. In order to translate the same rotational mechanism in a versatile sensor of polarity and viscosity, we designed and thoroughly characterized a novel FMR, namely 4-(triphenylamino)-phthalonitrile (TPAP). Remarkably, in addition to a high sensitivity versus solvent polarity and viscosity, TPAP is also able to form stable fluorescent nanoparticles characterized by aggregation-induced emission, via a simple sonochemical treatment. Such peculiar features are tested in different applications aiming at illustrating its capability to report on solvatochromic and vapochromic effects, as well as to provide detailed intracellular information through bioimaging studies.
CRIS-Team Scopus Importer:2023-03-07

Reactivity of a metastable cobalt(III) trisulfide complex: Multiple C-H functionalization of p-xylene and disulfides to afford photofunctional cobalt complexes - Maruyama, Masashi; König, Matthias; Guldi, Dirk Michael; Nakamura, Eiichi; Matsuo, Yutaka (Angewandte Chemie International Edition, 2013)
Unprecedented reactivity of a metastable cobalt trisulfide complex has been observed, and several direct C-S bond formation reactions by C-H functionalization were developed. These reactions produced a series of photofunctional motifs of sulfur-rich cobalt complexes (see picture). The measured photophysical properties of these complexes suggest promising molecular designs for photocurrent generating materials. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Reversible vapochromic response of polymer films doped with a highly emissive molecular rotor - Minei, Pierpaolo; König, Matthias; Battisti, Antonella; Ahmad, Muzaffer; Barone, Vincenzo; Torres, Tomas; Guldi, Dirk Michael; Brancato, Giuseppe; Bottari, Giovanni; Pucci, Andrea (Journal of Materials Chemistry C, 2014)
We report on a new vapochromic system suitable for sensing volatile organic compounds (VOCs) based on polymer films doped with 4-(diphenylamino)phthalonitrile (DPAP), a fluorescent molecular rotor sensitive to both solvent polarity and viscosity. Poly(methyl methacrylate) (PMMA) and polycarbonate (PC) films containing small amounts of DPAP (≤0.1 wt%) were prepared and exposed to saturated atmospheres of different VOCs. DPAP/PMMA films show a good and reversible vapochromism when exposed to VOCs with high polarity index and favourable interaction with polymer matrices such as THF, CHCl3, and acetonitrile. Analogously, DPAP/PC films exposed to polar and highly polymer-interacting solvents, that is, toluene, THF, and CHCl3, show a gradual decrease and red-shift of the emission. In contrast to DPAP/PMMA films, an unexpected increase and further red-shift of fluorescence are observed at longer exposure times as a consequence of an irreversible, solvent-induced crystallization process of PC. The vapochromism of DPAP-doped films is rationalized on the basis of alterations of the rotor intramolecular motion and polarity effects stemming from the environment, which, in concert, influence the deactivation pathways of the DPAP intramolecular charge transfer state. Overall, the present results support the use of DPAP-enriched plastic films as a new chromogenic material suitable for the detection of VOCs.
CRIS-Team Scopus Importer:2023-03-07

Selective synthesis of Co8S15 cluster in bowl-shaped template of the pentaaryl[60]fullerene ligand - Maruyama, Masashi; Imoto, Kenta; König, Matthias; Guldi, Dirk Michael; Ohkoshi, Shin-Ichi; Nakamura, Eiichi; Matsuo, Yutaka (Journal of the American Chemical Society, 2013)
A cobalt-sulfur cluster CoS with molecular formula of (CAr)-CoSBu-(CAr) (Ar = 4- BuCH) was selectively synthesized from a pentaaryl[60]fullerene cobalt trisulfide complex, (η-C Ar)CoS. The bowl-shaped steric templating fullerene ligand, as well as the metastable cobalt trisulfide moiety, played important roles in the exclusive cluster formation. X-ray crystallography, as well as electrochemical, time-resolved photophysical, and magnetic, measurements revealed a mixed-valence cluster with six cobalt(III) and two high-spin cobalt(II) centers showing reversible redox behavior and photoinduced charge separation. © 2013 American Chemical Society.

Synthesis, photophysical properties, and excited state dynamics of a platinum complex of tetracene imide disulfide - Nakagawa, Takafumi; Suzuki, Tsuyoshi; König, Matthias; Guldi, Dirk Michael; Matsuo, Yutaka (Chemical Communications, 2013)
A platinum complex containing a tetracene dicarboxylic imide disulfide (TIDS) was synthesized and structurally characterized by X-ray analysis. Steady-state absorption and emission spectroscopy for Pt-TIDS revealed its extended π-conjugated structure. Excited state studies characterized its triplet state with a lifetime of 0.18-0.28 μs. © 2013 The Royal Society of Chemistry.

Ultrasound-induced transformation of fluorescent organic nanoparticles from a molecular rotor into rhomboidal nanocrystals with enhanced emission - König, Matthias; Torres, Tomas; Barone, Vincenzo; Brancato, Giuseppe; Guldi, Dirk Michael; Bottari, Giovanni (Chemical Communications, 2014)
Fluorescent organic nanoparticles (FONs) based on aggregation-induced emission (AIE) are receiving increasing attention owing to their simple preparation, enhanced optical properties, and a wide range of applications. Therefore, finding simple methods to tune the structural and emissive properties of FONs is highly desirable. In this context, we discuss the preparation of highly emissive, amorphous AIE spherical nanoparticles based on a structurally-simple molecular rotor and their sonochemical transformation into rhomboidal nanocrystals. Interestingly, the ultrasound-induced modification of the morphology is accompanied by a remarkable enhancement in the stability and emission of the resulting nanocrystals. Detailed characterization of both spherical and rhomboidal nanoparticles was carried out by means of several microscopic, crystallographic, and spectroscopic techniques as well as quantum mechanical calculations. In a nutshell, this work provides a unique example of the ultrasound-induced switching of morphology, stability, and emission in FONs. © 2014 Partner Organisations.
CRIS-Team Scopus Importer:2023-03-07

Unraveling the peculiar modus operandi of a new class of solvatochromic fluorescent molecular rotors by spectroscopic and quantum mechanical methods - König, Matthias; Bottari, Giovanni; Brancato, Giuseppe; Barone, Vincenzo; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
A prototype for a new class of fluorescent molecular rotors (FMRs), namely 4-(diphenylamino)phthalonitrile (DPAP), was synthesized and its sensitivity towards solvent polarity and viscosity probed using photophysical and computational methods. DPAP is characterized by a pronounced fluorosolvatochromism in polarity-dependent absorption, emission and fluorescent lifetime experiments. At the same time, a strong viscosity response is observed, especially in polar and protic solvents. Quantum mechanical calculations assisted in interpreting the unusual solvent sensitivity of DPAP in terms of its high flexibility, giving rise to solvent-independent, barrier-free rotations. As a matter of fact, the modus operandi in DPAP contrasts that of traditional FMRs involving twisted intramolecular charge transfer (TICT) states. The influence of this unusual flexible character on excitation and emission energies was studied using computational methods upon considering twisting of the molecule in solvents of different polarity. Furthermore, a detailed characterization of the excited state profile was attained using time resolved spectroscopy techniques. In particular, a contrasting deactivation pattern of the intramolecular charge transfer (ICT) state was observed in low and high polar media. Moreover, in low and medium polar solvents strong emission is accompanied by triplet excited state formation, while in high polar and protic solvents the ICT state is highly stabilized and decays primarily non-radiatively. Notably, a viscosity increase in the latter solvents hampers rotations leading to a strong emission enhancement. This latter behavior, coupled to a remarkable solvatochromic character, makes DPAP a promising probe for biological and environmental sensing and imaging applications. © 2013 The Royal Society of Chemistry.